Unmet need for mental health care among adolescents in Asia and Europe - Mori, Yuko; Sourander, Andre; Mishina, Kaisa; Ståhlberg, Tiia; Klomek, Anat Brunstein; Kolaitis, Gerasimos; Kaneko, Hitoshi; Li, Liping; Huong, Mai Nguyen; Praharaj, Samir Kumar; Kyrrestad, Henriette; Lempinen, Lotta; et al. (Springer Nature, 2025)
The unmet need for mental health care is a global concern. There is a lack of cross-cultural studies examining adolescent help-seeking behavior from both formal and informal sources, including both high-and lower-income countries. This study investigates mental health help-seeking behavior in eight Asian and European countries. Data from 13,184 adolescents aged 13-15 (51% girls) was analysed using mixed-effects logistic regression with school-wise random intercepts to compare countries and genders. Although a significant proportion of adolescents considered getting or sought informal help, formal help-seeking remained exceptionally low, especially in middle-income countries (< 1%), while it ranged from 2 to 7% in high-income countries. Among adolescents with high emotional and behavioral problems (scoring above the 90th percentile on the Strengths and Difficulties Questionnaire), 1-2% of those in middle-income countries and 6-25% of those in high-income countries sought formal help. Girls generally seek more help than boys. The study shows the most adolescents do not receive formal help for mental health problems. The unmet need gap is enormous, especially in lower-income countries. Informal sources of support, including relatives, peers, and teachers, play a crucial role, especially in lower-income countries.